Biomonitoring of chlorinated polyfluoroalkyl ether sulfonic acid in the general population in central and eastern China: Occurrence and associations with age/sex. (November 2020) - Jin, Qi; Ma, Jinghong; Shi, Yali; Chen, Chuyi; Wang, Yuan; Zhao, Erjuan; Cai, Yaqi; Qu, Guoqiang
Graphical abstract: Highlights: The serum-to-whole-blood ratio of 6:2 Cl-PFESA was firstly investigated. 6:2 Cl-PFESA was observed as the third-highest contributing PFAS in the investigated population. 6:2 Cl-PFESA displays significantly increasing levels with increasing age. Males display higher levels of 6:2 Cl-PFESA than females. Abstract: Although chlorinated polyfluoroalkyl ether sulfonic acid (Cl-PFESA) has been reported to be widespread in different environmental matrices of China, its exposure data in the general Chinese population are very limited. In the present study, the serum-to-whole-blood ratio was first assessed for 6:2 Cl-PFESA (mean/median: 2.07/1.82) based on its paired concentrations (n = 36), which allows a comparison in different blood matrices. The exposure levels of Cl-PFESAs in the general population were investigated by collecting blood samples (n = 1516) from residents of seven cities in central and eastern China. 6:2 Cl-PFESA was observed as the third-highest contributing polyfluoroalkyl substance (PFAS) (8.69%), with the median concentration at 2.18 ng/mL, indicating its importance for assessing the human exposure risks of PFASs. The regional difference between 6:2 Cl-PFESA and perfluorooctane sulfonate (PFOS) can be explained by their use pattern in China. Overall, similar to PFOS, 6:2 Cl-PFESA displays significantly increasing levels with increasing age for both males and females, with significantly higher levels in males. However, a significant sex dependence was found for 6:2 Cl-PFESA in one specific age group (41–60), while there was no significance in the other groups although males display higher levels than females. Our study provides robust data regarding human exposure to 6:2 Cl-PFESA in the general population in central and eastern China.